CsWRKY25 Improves Resistance of Citrus Fruit to Penicillium digitatum via Modulating Reactive Oxygen Species Production - Wang, Wenjun; Li, Ting; Chen, Qi; Yao, Shixiang; Deng, Lili; Zeng, Kaifang (Frontiers in Plant Science, 2022)
WRKY transcription factors (TFs) play crucial roles in the regulation of biotic stress. Citrus is the most productive fruit in the world. It is of great value to investigate the regulatory molecular mechanism of WRKYs in improving disease resistance. In this research, the transcription level of CsWRKY25 was upregulated in P. digitatum infected citrus peel, and CsWRKY25 activated the expression of three target genes (RbohB, RbohD, and PR10). Besides, the Agrobacterium-mediated transient overexpression of CsWRKY25 has also been shown to enhance resistance to P. digitatum in citrus, and caused the accumulation of hydrogen peroxide and lignin. The accumulation of ROS also activated the antioxidant system, the catalase (CAT), peroxidase (POD), and cinnamyl alcohol dehydrogenase (CAD) genes were significant upregulated, leading to activation of antioxidant enzymes. In addition, the up-regulated expression of MPK5 and MPK6 genes suggested that the regulatory role of CsWRKY25 might be related to the phosphorylation process. In conclusion, CsWRKY25 could enhance the resistance to P. digitatum via modulating ROS production and PR genes in citrus peel.